Prevalence and Management Trends of Primary Dysmenorrhea among Adolescent Girls - Saira Naseem, Aaisha Aman, Fatima Sarwar, Aisha Nazeer, Nadia zulfiqar, Mubeen Ahmad Danial, Rakhshinda Inam Khan (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Primary dysmenorrhea constitutes a prevalent form of dysmenorrhea experiencedpredominantly by young girls in their adolescent years. Furthermore, it is frequently overlooked,even though it has significant consequences on educational achievement and routine activities. One of the most significant prerequisites